Management of traveller’s diarrhoea with a combination of sodium butyrate, organic acids, and A-300 silicon dioxide - Krokowicz, Lukasz; Mackiewicz, Jacek; Wejman-Matela, Anna; Krokowicz, Piotr; Drews, Michal; Banasiewicz, Tomasz (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Introduction: Traveller’s diarrhoea (TD), defined by UNICEF/WHO as three or more unformed stools with or without other symptoms, imposes a considerable burden on travellers from developed countries. Various efforts have focused on decreasing the prevalence and severity of this condition. Aim: To assess the efficacy of a combination of sodium butyrate, organic acids, and A-300 silicon dioxide in treatment providing symptomatic relief of TD. Material and methods : The study was conducted in accordance with a protocol presented to the Bioethical committee of Poznan University of Medical Sciences. A total of 278 patients travelling to countries with higher risk of diarrhoea for at least 10 days were divided into a study arm being administered, in case of TD, a combination of sodium butyrate, organic acids, and A-300 silicon dioxide (n = 139) and a  placebo arm (n = 139) with placebo administration. Results: Forty-seven patients completed the study (22 in the study arm and 25 in the placebo arm). The diarrhoea occurrence after initiation of treatment at first symptoms was significantly lower in the study arm as compared to the placebo arm (9% vs. 36%, p = 0.041). Also, subjects from the study arm more frequently reported that the regimen administered had been efficient for their symptoms in comparison to the placebo arm (72.7% vs. 32%, p = 0.008). No adverse effects of the administered medication were noted during the study. Conclusions : Sodium butyrate, organic acids, and A-300 silicon dioxide can be successful in decreasing symptoms of TD. Because of its efficacy and lack of observed side effects it has a strong potential in the treatment of patients with TD.